Restoration of a functional antiviral immune response to chronic HBV infection by reducing viral antigen load: if not sufficient, is it necessary? - Sisi Yang; Wanjia Zeng; Jiming Zhang; Fengmin Lu; Jinhong Chang; Ju-Tao Guo (Emerging Microbes and Infections)
The prolonged viral antigen stimulation is the driving force for the development of immune tolerance to chronic hepatitis B virus (HBV) infection. The sustained reduction of viral proteins may allow for the recovery and efficient activation of HBV-specific T and B cells by immune-stimulating agents, checkpoint blockades and/or therapeutic vaccinations. Recently, several therapeutic approaches have been shown to significantly reduce intrahepatic viral proteins and/or circulating HBV surface antigen (HBsAg) with variable impacts on the host antiviral immune responses in animal models or human clinical trials. It remains to be further investigated whether reduction of viral protein expression or induction of intrahepatic viral protein degradation is more efficacious to break the immune tolerance to chronic HBV infection. It is also of great interest to know if the accelerated clearance of circulating HBsAg by antibodies has a long-term immunological impact on HBV infection and disease progression. Although it is clear that removal of antigen stimulation alone is not sufficient to induce the functional recovery of exhausted T and B cells, accumulating evidence suggests that the reduction of viral antigen load appears to facilitate the therapeutic activation of functional antiviral immunity in chronic HBV carriers. Based on a systematic review of the findings in animal models and clinical studies, the research directions toward discovery and development of more efficacious therapeutic approaches to reinvigorate HBV-specific adaptive immune function and achieve the durable control of chronic HBV infection, i.e. a functional cure, in the vast majority of treated patients are discussed.